Antitumor Effects of Berberine on Gliomas via Inactivation of Caspase-1-Mediated IL-1β and IL-18 Release - Tong, Lei; Xie, Chuncheng; Wei, Yafen; Qu, Yunyue; Liang, Hongsheng; Zhang, Yiwei; Xu, Tianye; Qian, Xin; Qiu, Huijia; Deng, Haoyu (Frontiers in Oncology, 2019)
Gliomas is one of the most prevalent and devastating type of brain tumors. Studies of inflammatory response have established the importance of tumor micro-environment as a driven factor of oncogenesis. Inflammatory mediators such as IL-1β and IL-18 working via intracellular signaling pathways regulate hubs of transcriptional networks that are required for malignant cell growth. Berberine is a naturally botanical alkaloid that is widely found in the Berberis species. Although it has been widely used for anti-diarrheal treatment for several decades, our study first suggests that berberine has an anti-tumor effect on gliomas. Our results demonstrated that berberine significantly inhibits caspase-1 activation and subsequent production of IL-1β and IL-18. Moreover, we found that berberine treatment significantly leads to the death of U251 and U87 cells and disruption of their migration. Besides, our study first indicates that berberine can reverse the process of epithelial–mesenchymal transition, a marker of tumor invasion. In terms of mechanism, our study demonstrated that berberine regulates caspase-1 activation via ERK1/2 signaling. Taken together, our work first proposes that berberine may serves as an anti-tumor agent against gliomas.